Newport: Enabling Sharing During Mobile Calls - Gunaratne, Junius A.; Brush, A.J. (CHI 2010, 2010)
Newport is a collaborative application for sharing context (e.g. location) and content (e.g. photos and notes) during mobile phone calls. People can share during a phone call and sharing ends when the call ends. Newport also supports using a computer during a call to make it easier to share content from the phone or launch screen sharing if the caller is also at a computer. We describe Newport’s system design and a formative evaluation with 12 participants to study their experience using Newport to share location, receive directions, share photos, and perform desktop sharing. Participants preferred using Newport to current methods for these tasks. They also preferred limiting sharing location to phone calls compared with publishing it continuously. Tying sharing to a phone call gives individuals a social sense of security, providing a mechanism for exchanging information with unknown people.